The Impact of the Pandemic on Child and Adolescent Mental Health: A Systematic Assessment - Nair, Vineet (Journal of Social Science and Humanities, 2025)
The present paper aims to explore the impact of the COVID - 19 pandemic on the mental health of children and adolescents based on individual counselling sessions conducted under the Are You Okay program. The target population for the study were students from 7th Std to 10th Std. (Some children were left out in the beginning phase, as they opted for online classes for an extended period). Are You Okay program started in February 2021 and continued till March 2022. A total number of 550 students attended the individual counselling sessions. A phenomenological approach is taken to give shape to the research. As in the research, human experience during the phase of a pandemic is focused, thematic analysis is used for data collection and analysis. The data were analysed using systematic text condensation leading to two themes based on individual counselling, observation, and diary notes.1) The common themes depicting the positive impact on the mental health of children and adolescents, and 2) the common themes depicting the negative impact on the mental health of children and adolescents. The study reveals both positive and negative effects on mental health, with the detrimental effects being conspicuous. The paper also attempts to discuss coping strategies for long - term benefits. The findings of the present paper would help to bring back focus on children's mental health and to make it a priority. It could help professionals to train children to develop characteristics such as resilience, and to cope with problems in ever - changing world in an effective manner.